2013
DOI: 10.1136/sextrans-2013-051184.0801
|View full text |Cite
|
Sign up to set email alerts
|

P3.348 Maternal and Congenital Syphilis Remain a Challenge

Abstract: Conclusion These data suggest a high burden of TV and co-infection with CT. Public health surveillance focusing on CT infection may consider routine screening of other STIs, including TV, in local populations to reduce STI morbidity. Saúde do Distrito Federal, Brasília, Brazil This descriptive study set the profile of pregnant with positive VDRL followed at public maternity hospitals in Federal District, Brazil, of the newborns children of mothers with syphilis that showed clinic signs of congenital diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 0 publications
1
8
0
2
Order By: Relevance
“…Essa mesma estratégia de testagem, se aplicada aos parceiros, permitiria maior cobertura de tratamento, que é relatada como baixa em vários estudos locais 14,15,18,32,33 , sendo de apenas 11% no Brasil, segundo dados do SINAN para o ano de 2011 9 . Ressalta-se que o tratamento do parceiro é fundamental para evitar a reinfecção da gestante, sendo a não realização deste tratamento, ou a realização de tratamento inadequado, um dos critérios adotados pelo Ministério da Saúde para a definição de caso de sífilis congênita 2 .…”
Section: Discussionunclassified
“…Essa mesma estratégia de testagem, se aplicada aos parceiros, permitiria maior cobertura de tratamento, que é relatada como baixa em vários estudos locais 14,15,18,32,33 , sendo de apenas 11% no Brasil, segundo dados do SINAN para o ano de 2011 9 . Ressalta-se que o tratamento do parceiro é fundamental para evitar a reinfecção da gestante, sendo a não realização deste tratamento, ou a realização de tratamento inadequado, um dos critérios adotados pelo Ministério da Saúde para a definição de caso de sífilis congênita 2 .…”
Section: Discussionunclassified
“…Studies of similar shape and objectives conducted in maternity hospitals in different regions of Brazil, reported congenital syphilis rates varying from 1.3% to 14.5%. [17][18][19][20][21][22] Domingues et al, 23 in a national hospital based study in a sample of 450 newly delivered The monitoring of newborns from VDRL Lopes ID 21 Based on the 2012 guidelines of the Scientific Department of Nutrology, 28 86.8% of newborns in this study gained weight daily in their first month of life, greater than 15g per day. Only 14.2% gained less than 15g daily.…”
Section: ■ Discussionmentioning
confidence: 99%
“…This plan established the right of all pregnant women to carry out the VDRL test in the first prenatal consultation, third trimester of pregnancy and on admission for childbirth. 6 Despite the implementation of these WHO recommended actions, some studies have shown that, in the last decade, the incidence of congenital syphilis has increased globally, even in developed countries. These studies indicate, according to regions or countries, some factors that may or may not have contributed to its occurrence: the difficult access to prenatal care and/or its low quality; early sexual initiation; low income; use of legal and illegal drugs; sex professionals; low education, the non-partner treatment, among others.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such situation can be explained by the lower number of pre-natal consultations, insufficiency of resources for transportation to the laboratories and basic health units (UBS), and lack of financial support, and many others. Magalhães et al (2013) also found that 80.6% of the pregnant women studied had family income of up to four minimum salaries, concluding that syphilis, even if not being a disease that is restricted to the least privileged classes, is related to the low social-economic level and therefore, public health policies must be implemented to help pregnant women in this sense.…”
Section: Discussionmentioning
confidence: 99%